2022
DOI: 10.3389/fpsyg.2022.847099
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Posttraumatic Growth in Victims of Terrorism in Spain

Abstract: BackgroundScientific literature on posttraumatic growth (PTG) after terrorist attacks has primarily focused on persons who had not been directly exposed to terrorist attacks or persons who had been directly exposed to them, but who were assessed few months or years after the attacks.MethodsWe examined long-term PTG in 210 adults directly exposed to terrorist attacks in Spain a mean of 29.6 years after the attacks (range: 2–47 years). The participants had been injured by a terrorist attack (38.6%) or were first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…They know all too well that it can, and their new assumptive world is rebuilt acknowledging this very real possibility in the future". Thus, the inverted U-shaped relationship between the PTG and positive -or negative-core beliefs or attitudes is much more likely to be found when the PTG is examined over the long term (e.g., five or more years after the traumatic event; Fausor et al, 2022) rather than when examined in the short or medium term.…”
Section: R E S U M E Nmentioning
confidence: 99%
See 2 more Smart Citations
“…They know all too well that it can, and their new assumptive world is rebuilt acknowledging this very real possibility in the future". Thus, the inverted U-shaped relationship between the PTG and positive -or negative-core beliefs or attitudes is much more likely to be found when the PTG is examined over the long term (e.g., five or more years after the traumatic event; Fausor et al, 2022) rather than when examined in the short or medium term.…”
Section: R E S U M E Nmentioning
confidence: 99%
“…The sample of participants in this study is the same that participated in the study by Fausor et al (2022). A sample of 210 adults who had been injured in a terrorist attack or who were relatives of people who had died or had been injured in an attack was recruited from members of the Association of Victims of Terrorism (AVT) of Spain.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, an average of 14.5 years had passed between the most traumatic event that the participants had experienced and the time of assessment. Thus, it might be the case that the lack of a quadratic relationship between PTG and posttraumatic stress symptoms is specific to long-term PTG (cases in which it has been at least five years since the traumatic experience), as suggested by the results of this study and those of Fausor et al (2022).…”
Section: Discussionmentioning
confidence: 71%
“…Another limitation is connected to questions about the possibility of assessing PTG after an average of 14.5 years since the traumatic experience. This limitation is discussed in greater detail in Fausor et al (2022) and Liébana et al (2022), and it suggests that future research should examine the degree of consistency between self-reported PTG and the changes observed in a person by his or her family, friends and colleagues. Such research should also include a control group to ensure that the growth recorded is really a result of the event and not merely of the passage of time.…”
Section: Discussionmentioning
confidence: 99%